Jules Lavirotte (1864-1929) ou l’Art nouveau symboliste - Bruno Montamat (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Built from 1898 to 1901 in Paris, the buildings of Avenue Rapp by Jules Lavirotte (1864-1929) are as well known as little studied. Although rehabilitated since the 1960s, Art Nouveau remains a formidable moment of aesthetic and social utopia whose spiritual foundations remain unclear, due in particular to the lack of primary sources. The study of unpublished family archives from the architect’s wife, the painter Jane de Montchenu (1857-1924) allows the writing of a sensitive biography, more able to grasp the exuberance of an idealistic architectural signature. Its inscription in a late-century symbolism opens up promising new fields of research by taking into account the sacred in private architecture and by the emancipatory role played by female artist. It would illustrate the dissemination at work of theosophical ideas in the formal development of the first current of Art Nouveau, Modern style.